Utilizing facilitative mediation for the resolution of inter-state conflicts - Belano, Zoilo D. Jr. (2016)
The significance of mediation as a system of conflict resolution in international arena has been well-documented and emphasized. It has assisted in resolving inter-state conflicts. Vukovic (2011:114) elaborates three factors that may influence international mediation; firstly, mediator's characteristics such as impartiality, interests and leverage; secondly, contextual: type of conflict, characteristics of the disputing sides or geopolitical/ systematic dynamics; and thirdly, behavioral which deals with mediation strategies. Beardsley, et al. (2006:59) identify three mediation strategies according to the intensify of intervention, namely; facilitation as less invasive strategy, formulation as middle invasive strategy, and manipulation as the highly invasive strategy. The main focus of this article is the discussion on facilitation (facilitative) or what Touval and Zartman (as cited in Bercovitch 2002:16) referred to as communication-facilitation mediation; and what Martin (2007:35) also called as interest-based, problem solving mediation. The challenges and advantages of using facilitative mediation in international conflict resolution are elaborated.
Keywords: Conflict management; Conflict resolution